2006
DOI: 10.3354/meps312029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrient enrichment and shading on sediment primary production and metabolism in eutrophic estuaries

Abstract: -1). Nutrient enrichment had little effect on sediment primary production and metabolism in the estuarine sites studied; however, in some instances nutrient enrichment influenced the negative effects of reduced light on sediment net production. The results demonstrate that the impact of light reduction on sediment primary production and metabolism in a turbid, nutrient-rich estuary is greater than that of additional sediment nutrient enrichment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 63 publications
2
38
0
Order By: Relevance
“…Light availability (represented by the attenuation coefficient) was the primary control on sediment GPP and NCP in our shallow study lagoons (Table 4), driving 24 and 31% of the variability in these rates, respectively, a pattern also reported in other shallow systems (Stutes et al 2006, Murrell et al 2009). Based on measurements by the component method, pelagic metabolism dominated the NEM signal (in a 1 m water column).…”
Section: Component Metabolismsupporting
confidence: 72%
See 1 more Smart Citation
“…Light availability (represented by the attenuation coefficient) was the primary control on sediment GPP and NCP in our shallow study lagoons (Table 4), driving 24 and 31% of the variability in these rates, respectively, a pattern also reported in other shallow systems (Stutes et al 2006, Murrell et al 2009). Based on measurements by the component method, pelagic metabolism dominated the NEM signal (in a 1 m water column).…”
Section: Component Metabolismsupporting
confidence: 72%
“…The excretion of extracellular polymeric substances by MPB should reduce resuspension (MacIntyre et al 1996, Lucas et al 2001), but strong winds or tides can overcome this effect (Shaffer & Sullivan 1988, MacIntyre et al 1996. Without taxonomic distinction, we cannot be certain of the contribution of resuspended MPB to water column metabolism, but resuspended MPB can increase pelagic production and reduce sediment production through shading (MacIntyre et al 1996).Light availability (represented by the attenuation coefficient) was the primary control on sediment GPP and NCP in our shallow study lagoons (Table 4), driving 24 and 31% of the variability in these rates, respectively, a pattern also reported in other shallow systems (Stutes et al 2006, Murrell et al 2009). Based on measurements by the component method, pelagic metabolism dominated the NEM signal (in a 1 m water column).…”
supporting
confidence: 71%
“…Weeks Bay, Alabama, in the northern Gulf of Mexico (30° 45' N, 87° 88' W), is a subestuary of Mobile Bay (Stutes et al 2006). Its surface area is 8 km².…”
Section: Methodsmentioning
confidence: 99%
“…Measurements taken 1 h after adding the nutrients revealed that immediate increases in nutrient concentration were variable (Table 3), ranging on average from 2-to 9-fold among experiments for DIN and from 2-to 5-fold for DIP. Discrepancies between targeted and realized increases in nutrient concentration often occur in fertilization experiments due to factors that are not well known and/or cannot be controlled with accuracy , Stutes et al 2006). Here, it is possible that nutrient efflux from the settling sediment into the overlying water within the aquaria may have contributed to the higher level of enrichment found in some of the experiments (Sundbäck et al 1991, Rizzo et al 1992, Hardison et al 2010.…”
Section: Methodsmentioning
confidence: 99%